Potential impact of climate change on the global geographical distribution of the invasive species, Cenchrus spinifex (Field sandbur, Gramineae). (November 2021) - Cao, Jing; Xu, Jun; Pan, Xubin; Monaco, Thomas A.; Zhao, Kun; Wang, Deping; Rong, Yuping
Highlights: The potential geographical distribution indicates a significant increase in future. Sandy soils of seacoast provide the suitable habitats for establishment. Precipitation is the key factor affecting its potential distribution. Abstract: Field sandbur ( Cenchrus spinifex Cav.) is an annual grass native to North America that has spread widely in South America, Europe, Asia, Australia and other regions, reducing crop and grassland productivity. In recent decades, global climate change and human activity have been linked to the spread of C. spinifex and its impact on ecosystem and biodiversity. In order to characterize the role of climate change on this trend and highlight regions of high invasion risk, we used global distribution data and maximum entropy models (MaxEnt) to analyze suitable habitats based on four global climate models and two representative concentration pathways under different climate scenarios. Receiver operating characteristic (ROC) curve analysis method was also used to further verify the prediction accuracy of the model, which was statistically significant (AUC = 0.921). Climatically suitable areas of C. spinifex at present climate conditions were located at six continents including central South America, southern parts of North America and Africa, most of Mediterranean coastal European regions, Asia, Australia, and New Zealand. Future climate conditions may promote C. spinifex expansion into coastal regions. Meanwhile, C. spinifex in the northern hemisphere were expected to spread further southward (20-55°N; 30-55°S) compared to present potential geographical distribution. The suitable habitat area of C. spinifex would be slightly reduced in 2050 and 2070. Seasonal precipitation, precipitation of driest quarter (bio15, bio17) and mean temperature of warmest and coldest quarter (bio10, bio11) could be the major environmental variables affecting the potential distribution of C. spinifex . Preventing the spread of C. spinifex in the future will require strict phytosanitary measures to reduce colonization of new regions, such as Japan, India, Russia, and Thailand. Our research provides a foundation to focus future management efforts and prioritize area of greatest ecological concern.